2007
DOI: 10.1007/s10557-007-6018-2
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism Underlying Vascular Smooth Muscle Cell Apoptosis Induced by Atorvastatin may be Mainly Associated with Down-regulation of Survivin Expression

Abstract: Atorvastatin induces VSMCs apoptosis in a dose- and time-dependent manner. Transfection of survivin ASODN can directly induce VSMCs apoptosis. The mechanisms of VSMCs apoptosis induced by atorvastatin may be mainly associated with down-regulation of survivin expression in VSMCs. Up-regulation of Fas in VSMCs may play a role in later stages following atorvastatin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Similar to the result by Simosa et al (2005) that delivery of survivin mutants (AdT34A) after balloon injury attenuated neointimal hyperplasia, Daniel et al (2012) revealed that survivin played a crucial role in inhibiting the proliferative response of VSMCs and neointima formation mediated by a highly potent inhibitor of transcription-3. In addition, our previous in vitro experiment found that VSMCs apoptosis induced by atorvastatin may be mainly associated with down-regulation of survivin expression (Xu et al, 2007). In line with the above investigations, the present in vivo study identified that the inhibition of neointimal proliferation by atorvastatin may closely be related to VSMCs apoptosis and down-regulation of survivin levels after vascular injury.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the result by Simosa et al (2005) that delivery of survivin mutants (AdT34A) after balloon injury attenuated neointimal hyperplasia, Daniel et al (2012) revealed that survivin played a crucial role in inhibiting the proliferative response of VSMCs and neointima formation mediated by a highly potent inhibitor of transcription-3. In addition, our previous in vitro experiment found that VSMCs apoptosis induced by atorvastatin may be mainly associated with down-regulation of survivin expression (Xu et al, 2007). In line with the above investigations, the present in vivo study identified that the inhibition of neointimal proliferation by atorvastatin may closely be related to VSMCs apoptosis and down-regulation of survivin levels after vascular injury.…”
Section: Discussionsupporting
confidence: 89%
“…However, agents currently in more widespread clinical use might also have a role. Thus HMG-Co-A reductase inhibitors (statins) have been reported to inhibit phosphate-induced apoptosis of smooth muscle cells [93], but the evidence is ambiguous [94,95] and simvastatin did not reverse established arterial calcification in one human study [96]. The potential benefit of peroxisome proliferatoractivated receptor (PPAR)γ agonists has yet to be fully explored, although their use is known to be associated with decreased expression of pro-inflammatory cytokines and they have also been reported to inhibit neovascularisation.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…A second pathway involved in SMC apoptosis is represented by the p53/p21 WAF1/Cip1 proteins; however, the induction of apoptosis by statins seems to be independent of p53 [147]. Another possible mechanism of statin-induced apoptosis has been finally proposed by the group of Xu, who described the downregulation of the expression of the antiapoptotic protein survivin by atorvastatin [148].…”
Section: Effect Of Statins On Apoptosis Of Smooth Muscle Cellsmentioning
confidence: 99%